2006
DOI: 10.1128/aem.02842-05
|View full text |Cite
|
Sign up to set email alerts
|

Functional Heterogeneity of RpoS in Stress Tolerance of Enterohemorrhagic Escherichia coli Strains

Abstract: The stationary-phase sigma factor (RpoS) regulates many cellular responses to environmental stress conditions such as heat, acid, and alkali shocks. On the other hand, mutations at the rpoS locus have frequently been detected among pathogenic as well as commensal strains of Escherichia coli. The objective of this study was to perform a functional analysis of the RpoS-mediated stress responses of enterohemorrhagic E. coli strains from food-borne outbreaks. E. coli strains belonging to serotypes O157:H7, O111:H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 56 publications
2
39
0
2
Order By: Relevance
“…The rpoS gene is polymorphic in E. coli (6,27), as well as in other gammaproteobacteria (39). Despite the reported high sequence variability of the rpoS gene, we found that the frequency of synonymous mutations in the fliA gene, encoding another nonessential sigma factor, was comparable to that of the rpoS gene.…”
Section: Discussionmentioning
confidence: 99%
“…The rpoS gene is polymorphic in E. coli (6,27), as well as in other gammaproteobacteria (39). Despite the reported high sequence variability of the rpoS gene, we found that the frequency of synonymous mutations in the fliA gene, encoding another nonessential sigma factor, was comparable to that of the rpoS gene.…”
Section: Discussionmentioning
confidence: 99%
“…The genotype-determined phenotypic effects of within-species variation are indeed profound, so one strain of E. coli can have a very different response to the same level of stress than another (24,98) or a very different growth rate or competitive ability in particular environments (157). Genomics efforts have highlighted the relatively small core genome and the relatively large pan-genome within a species such as E. coli (193,348), so it is highly likely that some of the pan-genome differences will affect adaptive responses.…”
Section: Importance Of the Genotype In Determining The Nature Of Adapmentioning
confidence: 99%
“…For example, naturally occurring strains can differ in the amount of RpoS they produce during exponential phase (12) or stationary phase (13). All studies that have measured RpoS levels in naturally occurring strains of E. coli have detected variations (13)(14)(15)(16)(17), though the extent and cause of the variations in RpoS between strains is still a matter of some controversy (16,17).…”
mentioning
confidence: 99%